Ultralow Impedance Graphene Microelectrodes with High Optical Transparency for Simultaneous Deep Two‐Photon Imaging in Transgenic Mice. (5th June 2018) - Lu, Yichen; Liu, Xin; Hattori, Ryoma; Ren, Chi; Zhang, Xingwang; Komiyama, Takaki; Kuzum, Duygu
Abstract: The last decades have witnessed substantial progress in optical technologies revolutionizing our ability to record and manipulate neural activity in genetically modified animal models. Meanwhile, human studies mostly rely on electrophysiological recordings of cortical potentials, which cannot be inferred from optical recordings, leading to a gap between our understanding of dynamics of microscale populations and brain‐scale neural activity. By enabling concurrent integration of electrical and optical modalities, transparent graphene microelectrodes can close this gap. However, the high impedance of graphene constitutes a big challenge toward the widespread use of this technology. Here, it is experimentally demonstrated that this high impedance of graphene microelectrodes is fundamentally limited by quantum capacitance. This quantum capacitance limit is overcome by creating a parallel conduction path using platinum nanoparticles. A 100 times reduction in graphene electrode impedance is achieved, while maintaining the high optical transparency crucial for deep two‐photon microscopy. Using a transgenic mouse model, simultaneous electrical recording of cortical activity with high fidelity is demonstrated while imaging calcium signals at various cortical depths right beneath the transparent microelectrodes. Multimodal analysis of Ca 2+ spikes and cortical surface potentials offers unique opportunities to bridge our understanding of cellular dynamics and brain‐scale neural activity. Abstract : Ultralow impedance graphene microelectrodes with high optical transparency are developed for simultaneous electrophysiology and deep two‐photon imaging in transgenic mice. Quantum capacitance is demonstrated to be the cause of high impedance of monolayer graphene microelectrodes. Deposition of platinum nanoparticles on monolayer graphene surface decreases the impedance by 100 times while maintaining the high optical transparency crucial for deep two‐photon microscopy.